The Relationship between Regulatory Environment, Social Capital, Infrastructure, and Entrepreneurial Success on the Performance of Indonesian MSMEs - Junaedi, I Wayan Ruspendi; Sumastuti, Efriyani; Harsono , Iwan (MultiTech Publisher, 2024)
This research investigates the intricate relationships between the regulatory environment, social capital, infrastructure, and entrepreneurial success in Indonesian Micro, Small, and Medium-sized Enterprises (MSMEs). Employing Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis on a diverse sample of 200 businesses, the study unravels the direct and indirect effects of these factors. Results indicate that a favorable regulatory environment, robust social capital, and adequate infrastructure significantly contribute to the success of MSMEs. Furthermore, social capital and infrastructure act as mediators, magnifying the impact of the regulatory environment on entrepreneurial success. These findings carry practical implications for policymakers and practitioners seeking to enhance the MSME ecosystem in Indonesia